2014
DOI: 10.1177/0309816814533291
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the special section: Urban neoliberalism, strategies for urban struggles, and ‘the right to the city’

Abstract: The strategy and demand for the ‘right to the city’ was first advanced by Henri Lefebvre in the late-1960s. The concept has been used as a slogan by urban movements in various countries since the 2000s, and has also been discussed in left academic literature. This special section of Capital & Class contains interviews on contemporary urban politics and the right to the city by two Marxist urbanists, Neil Smith and Jamie Gough. These are preceded by a brief history by Jamie Gough of the idea and use of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Neoliberal politikalar altında ekonomik ve kentsel yeniden yapılanma ile konut finansal bir araç haline gelmiştir. Baskın özel sektör ve sermaye odaklı üretim, konut üretiminin sektöre dönüşmesine neden olmuştur (Çelik ve Gough, 2014;Marcuse ve Madden, 2016). Finansallaşan ve özelleştirilmiş konut sektörü ise, küresel ekonomiye daha fazla eklemlenmiştir (Forrest, 2008).…”
Section: Neoliberal Politikaların Konut üRetimine Etkisiunclassified
“…Neoliberal politikalar altında ekonomik ve kentsel yeniden yapılanma ile konut finansal bir araç haline gelmiştir. Baskın özel sektör ve sermaye odaklı üretim, konut üretiminin sektöre dönüşmesine neden olmuştur (Çelik ve Gough, 2014;Marcuse ve Madden, 2016). Finansallaşan ve özelleştirilmiş konut sektörü ise, küresel ekonomiye daha fazla eklemlenmiştir (Forrest, 2008).…”
Section: Neoliberal Politikaların Konut üRetimine Etkisiunclassified
“…Many scholars of critical urban theory have argued for the necessity of unity between different struggles as a way of moving toward a more radical urban politics (Blokland et al, 2015; Harvey, 2012; Mayer, 2013; Gough and , 2014). Many more have suggested that the RTC itself can act as a unifying concept (Harvey, 2012; Mitchell and Heynen, 2009; Purcell, 2013).…”
Section: The Contemporary Political Scene: Fragmentationmentioning
confidence: 99%
“…The rights-based approach seems to have the merit of uniting movements of diverse ideological orientations, thanks to its universalizing claim of the right to food, land and seeds. However, a major limitation of this approach is that these rights are permeated by liberal-hegemonic conceptions, which have the potential to ‘incorporate[s] no imperative to look beyond rights to the social relations that make any particular set of rights appear as common moral sense’ and render class agents ‘highly vulnerable to political co-option and the re-absorption of political protest into the goal of a reworked capitalism under the framework of existing liberal rights’ (Neil Smith interviewed in Çelik, 2014, p. 425). This issue adds to the fact that the rights regimes in place ‘are built around the obligations of states, and fail to adequately address the responsibilities of private and transnational actors’ (Claeys, 2014, p. 453).…”
Section: Recent Attempts To Resolve Theoretical Controversies: Class-mentioning
confidence: 99%